Disentangling the factors that vary the impact of trees on flooding (a review). (31st October 2020) - Marapara, Tapuwa R.; Jackson, Bethanna M.; Hartley, Stephen; Maxwell, Deborah
Abstract: There is growing interest in the role of trees and forests in reducing the risk of flooding. The establishment of forests and planting of trees changes surface and subsurface hydrology, often delaying peak discharge and reducing overland flow and flood risk. However, it is increasingly recognised that a blanket recommendation to 'plant trees' is rarely an efficient approach to flood‐risk management. This is because the role of trees varies spatially and temporally as a function of climate, topography, rainfall properties, soil type and condition, catchment scale and geology, among others. This paper presents a review of the complex relationship between tree cover and flooding. It discusses how the interaction is affected by species, position in the landscape, catchment scale, soils, magnitude of rainfall event and changing geologic and climatic conditions. Finally, it highlights how, when and where trees and forests can be effectively used to assist in managing the risk of flooding. Knowledge gaps that require future research are also identified.